2019
DOI: 10.3389/fgene.2019.00108
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis Reveals Key Circular RNA in Atrial Fibrillation

Abstract: Circular RNAs (circRNAs) are an emerging class of RNA species that may play a critical regulatory role in gene expression control, which can serve as diagnostic biomarkers for many diseases due to their abundant, stable, and cell- or tissue-specific expression. However, the association between circRNAs and atrial fibrillation (AF) is still not clear. In this study, we used RNA sequencing data to identify and quantify the circRNAs. Differential expression analysis of the circRNAs identified 250 up- and 126 down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…phenotypes, we think that the screening algorithm we used may be too strict, and the results may lose a large number of true positive results. Therefore, we changed the screening criteria, using the criteria of log2 (fold change) >1 or log2 (fold change) <−1 and P value <0.05 as previous studies (Dang et al, 2017;Xu et al, 2018;Hu et al, 2019) to screen out 112 different expression circRNAs between PS and NC, and then randomly selected 10 circRNAs for verification experiment. On the basis of verification, we calculated the false positive rate (FPR) to generate the Q value.…”
Section: Discussionmentioning
confidence: 99%
“…phenotypes, we think that the screening algorithm we used may be too strict, and the results may lose a large number of true positive results. Therefore, we changed the screening criteria, using the criteria of log2 (fold change) >1 or log2 (fold change) <−1 and P value <0.05 as previous studies (Dang et al, 2017;Xu et al, 2018;Hu et al, 2019) to screen out 112 different expression circRNAs between PS and NC, and then randomly selected 10 circRNAs for verification experiment. On the basis of verification, we calculated the false positive rate (FPR) to generate the Q value.…”
Section: Discussionmentioning
confidence: 99%
“…Though atrial fibrillation (AF) is the most common type of arrhythmia in the general population, ventricular arrhythmia (VA) is the major mechanism of SCD in IHD [ 57 , 98 ]. Some studies revealed that circRNAs participate in AF by the identification and characterization of circRNA expression profiles, and provide novel biomarkers and potential therapeutic targets for AF [ 99 ]. However, the expression and function of circRNAs in VAs were not experimentally confirmed.…”
Section: Circrna Serves As Biomarkers In Scd-related Diseasesmentioning
confidence: 99%
“…Another study revealed that the expression of circANRIL subtypes were inversely correlated with the risk and the severity of AS ( 85 ). Furthermore, a recent study documented for the first time the association between the expression of circRNAs and atrial fibrillation ( 86 ). Therefore, a total of five circRNAs were identified with notable biological significance, including chr9:15474007-15490122, chr16:75445723-75448593, hsa_circ_0007256, chr12:56563313-56563992 and hsa_ circ_0003533.…”
Section: Expression Of Circrnas In Cells Of the Cardiovascular Sysmentioning
confidence: 99%